Estimating the Asphalt Binder Film Thickness Using Scanning Electron Microscope and Energy Dispersive X-Ray Spectroscopy - Fazli Karim; Jawad Hussain; Imran Hafeez (Advances in Materials Science and Engineering)
Asphalt binder film thickness has relation to mixing temperature and binder content in hot mix asphalt, which influences mixture’s performance. A significant variation in assessing the asphalt binder film thickness has been observed in the literature. Development of state of the art technology and Superpave specification requires the study of actual asphalt binder film thickness at micro-level. This study estimates asphalt binder film thickness at micro-level and compares results with those obtained through analytical models from the previous studies. The study utilizes different asphalt mixtures at various mixing temperatures and binder contents. The asphalt binder film thickness around the finest particles of 500 nm (0.5 micron) size in asphalt mastic was detected and measured by image analysis (using scanning electron microscope) and elemental analysis (using energy dispersive X-ray spectroscopy) at magnifying power of ×30,000. The analytical estimation revealed that the asphalt binder film thickness for the aforementioned conditions varies from 9 μm to 13 μm, with a fair relationship to binder content and mixing temperature. However, results obtained from image analysis revealed that the asphalt binder film thickness varies from 0.5 μm to 2.4 μm, with no relation to binder content and mixing temperature. The image analysis showed that the asphalt mixtures mostly contain asphalt mortar and asphalt mastic, occurring in irregular shape. It was also found that the asphalt binder film does exist as a separate entity inside the asphalt mastic in the form of a band around the filler particles as non-absorbed binder, which fills the approximate distance of 0.5 to 2.5 microns among filler particles.